Visible-Light-Induced Cyclization of Electron-Enriched Phenyl Benzyl Sulfides: Synthesis of Tetrahydrofurans and Tetrahydropyrans - Li, Wei; Yang, Chao; Gao, Guo-Lin; Xia, Wujiong (Synlett, 2016)
A new approach to the preparation of tetrahydrofurans and tetrahydropyrans through a photoredox catalytic process is described. The introduction of a phenylsulfanyl auxiliary group permits the substrates to be readily oxidized to form cationic intermediates for sequential intramolecular cyclization. The method features mild reaction conditions and operational simplicity.
Keywords: photocatalysis; sulfides; cyclization; tetrahydrofurans; tetrahydropyrans